Design and Rationale of the Phase 3 ATTR-ACT Clinical Trial (Tafamidis in Transthyretin Cardiomyopathy Clinical Trial). (June 2017) - Maurer, Mathew S.; Elliott, Perry; Merlini, Giampaolo; Shah, Sanjiv J.; Cruz, Márcia Waddington; Flynn, Alison; Gundapaneni, Balarama; Hahn, Carolyn; Riley, Steven; Schwartz, Jeffrey; Sultan, Marla B.; Rapezzi, Claudio
Abstract : Transthyretin amyloidosis is a rare, life-threatening disease resulting from aggregation and deposition of transthyretin amyloid fibrils in various tissues. There are 2 predominate phenotypic presentations of the disease: transthyretin familial amyloid polyneuropathy, which primarily affects the peripheral nerves, and transthyretin cardiomyopathy (TTR-CM), which primarily affects the heart. However, there is a wide overlap with symptoms at presentation and disease course being highly variable and influenced by the underlying transthyretin mutation, age of the affected individual, sex, and geographic location. Treatment of transthyretin amyloidosis is typically focused on symptom management. Although tafamidis has been shown to delay neurologic progression of transthyretin familial amyloid polyneuropathy, there are no approved pharmacologic therapies shown to improve survival in TTR-CM. The natural history of TTR-CM is poorly characterized, which presents difficulties for the design of large-scale trials for new treatments. This review provides a brief overview of TTR-CM and the challenges of identifying clinically meaningful end points and study parameters to determine the efficacy of treatments for rare diseases. The design and rationale behind the ongoing phase 3 ATTR-ACT study (Tafamidis in Transthyretin Cardiomyopathy Clinical Trial), an international, multicenter, double-blind, placebo-controlled, randomized clinical trial, is also outlined. The ATTR-ACT study will provide important insight into the efficacy and safety of tafamidis for the treatment of TTR-CM. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01994889.